Performance profiles and opposition interaction during game-play in elite basketball: evidences from National Basketball Association - Zhang, S.; Lorenzo, A.; Zhou, C.; Cui. Y.; Gonçalves, B.; Gómez, M. A. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was two folds: (i) to explain the relationships between game-related statistics and game outcome based on team quality and (ii) to explore the effects of opposition interaction on the players` technical and physical performances according to playing position. Game-related statistics of all the 692 balanced games of regular season 2016-2017 in the National Basketball Association were analysed. All the analyses were conducted by decision-tree algorithm (exhaustive CHAID) and magnitude-based inferences. Our study indicated that defensive rebounds, blocked shots, and assists determined between winning and losing games for stronger teams while defensive rebounds and turnovers were the key performance indicators for weaker teams. Subsequently, in stronger vs stronger games, players from winning teams in home games ran slower than their peers from losing teams, whereas an opposite trend was found in away games. In stronger vs weaker games, players from winning teams in home games covered more distance and ran faster than their peers from losing teams. In weaker vs weaker games, effective defence played an important role in winning the games. The findings provide references for coaches and performance analysts to design training plans accounting for quality of teams and oppositions.